Agricultural information needs of women farmers in Mubi region, Adamawa State - Elizabeth, Sabo (Journal of Tropical Agriculture, 2008)
The information needs of women farmers in the Mubi region of Nigeria was evaluated in a multi-stage random sampling process involving 300 respondents registered with the Agricultural Development Project of Adamawa State in 2006. Results indicate that 76% of the respondents were below 40 years, and 50% were married. Sorghum, maize, cowpea, and groundnut were the common crops cultivated. The women farmers required information on weather, soil management, credit availability, and farm management, besides awareness on improved seedlings, fertilizer and insecticides, animal health, future market prices, land tenure, child immunization, and vaccination for animals. The inferential statistics indicate that the responses were not similar for most of the information resource needs. The information needs of women farmers in these locations should, therefore, be tailored along the preferred needs.